Odysseus in the serpent maze - Yolen, Jane.; Harris, Robert J., 1955- (New York, NY: HarperTrophy Publishers, 2001)
Young Odysseus, who longs to be a hero, has many chances to prove himself during an adventure which involves pirates and satyrs, a trip to Crete's Labyrinth, and two girls, Penelope and Helen, who play a role in his future.
1 9 12 13 19 38
Keywords: Adventure fiction; Classical mythology -- Fiction; Odysseus (Greek mythology) -- Fiction; Adventure and adventurers -- Fiction; Heroes and heroines -- Fiction; Young Hoosier Book Award Nominee 2003-2004